Significance and Connection of the Components of Medical Knowledge in the Context of the Paradigm Shift in Medicine - Sheraliyev Ilyosjon Ibroxim oʻgʻli; Raimqulov Rivoj Sobir oʻgʻli (Genius Journals, 2023)
In our article, historical research is analyzed to study ways and possible prospects for solving current problems in medicine and the development of medical sciences, as well as clinical, biochemical, experimental, psychological, and other methods of studying medical phenomena that historically arose as constantly evolving social institution and are subject to constant changes in the historical process. Throughout history, various paradigms have emerged in the system of humanity’s ontological views, theoretical views, beliefs, and values that unite members of the scientific community.
Keywords: paradigmatic; medicine; humanistic; pathogenesis